ANALISIS BIAYA JAMKESMAS DAN ASKES PADA PASIENSTROKE NON HEMORAGIK DI RUMAH SAKIT UMUM DAERAH KABUPATEN SLEMAN - , Manna, Prof. dr. Iwan Dwiprahasto, M.Med.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background Non-hemorrhagic stroke is a cause of many deaths and the treatment requires long-term care, resulting in a very high cost. Funding by health insurance either with prospective system (Jamkesmas) and the retrospective system (Askes), control costs and quality are very important in maintaining the sustainability program, but in reality there are cost sharing by patients and hospitals outside of the scope of insurance programs. Objective Toidentify the difference in the cost that must be shared to the patient and the hospital for inpatient non-hemorrhagic stroke of the Jamkesmas and Askes patients in Sleman hospital specificallyto measurethe averagecost, relations of patientfactor, service factor, anddrugfactorto thecost sharingand thetotalcost, the proportion offinancingcomponentscoveredandnot coveredandcompare the cost basedratesINA-CBGsandcostsbased hospital prices Method This study used observational methods crosectional descriptive design, data retrieved retrospectively with a primary diagnosis of non-hemorrhagic stroke hospitalizations that eligible criteria from patients admitted to the hospital for discharge during the period January 2011 to May. Data were analyzed using univariate, bivariate correlation, multivariate. Result The average cost of inpatient care non-hemorrhagic stroke Jamkesmas patients is Rp.3.541.021,- + 2.609.488 (influential factoris theLOSand sex) and in Askes patients is Rp.4.678.509,- + 3.257.816 (influential factors is Non DPHO and comorbidities).The average cost sharing in Askes patients is Rp.1.851.536,- + 1.968.757,- (influential factor is non DPHO, LOS andclass ward) and Jamkesmas is Rp.405.976 +2.303.903,- (influentialfactorsis LOS and sex). Percentage greatest cost component in Askes patients is drugs (47%) and accomodation (44%) and in Jamkesmas is the drug (52%) and accommodation (36%). Components of the cost sharing in Askes patients is the drug (87%). The difference in the cost of hospital rates greater than INA-CBGs respectively Rp.3.541.021 + 2.609.488 and Rp.3.135.045,- + 727.710,- ConclusionThe proportion of costs by the insurance covered and shared by patient/hospital is 87:13 for Jamkesmas patient, 55:45 for Askes patients the period January 2011-May 2011 , and 59:41 for the Askes patients the period June 2011-May 2012. The proportion ofcost sharingofinpatient carenon-hemorrhagic stroke by Askes patients outside the program is greater thanthe proportion ofcosts sharing by the hospital on Jamkesmas program.